Serum Adiponectin Levels In Patients Of Type 2 Diabetes Mellitus - Sheema Khan, Nasir Rashid, Aliya Muzaffar, Rukhsana Gulzar (Pakistan Journal of Medical & Health Sciences, 2022)
Aim: To find out the serum adiponectin levels in patients of type 2 diabetes and non diabetics. Methods: A cross-sectional, comparative study included 88 subjects. Out of 88 cases, 68 were diagnosed cases of T2DM. In 68 diagnosed cases, 34 were newly diagnosed cases of T2DM without any treatment and 34 were on oral hypoglycemic medicine. 20 subjects were controls which were age and sex matched. Serum adiponectin levels were estimated by using ELISA procedure. Total cases were divided into Group A: 34 newly diagnosed patients of T2DM without any treatment. Group B: 34 patients of T2DM on oral hypoglycemic medicine and Group C: 20 subjects of normal controls. Results: In our study, mean ± SD values of adiponectin levels in non-diabetics in Group C were 1560 ±1044.6 ng/ml. In group A, mean ± SD values of adiponectin levels were 1153±792.6ng/ml and in group B, mean ± SD values of adiponectin levels were 1601±1210.5ng/ml. The adiponectin levels were lower in diabetics without medication (A) as compared to the control group (C). The difference was statistically significant between groups A vs B and A vs C while the difference was statistically non significant between groups B vs C. Conclusion: The adiponectin levels were lower in diabetics without medication (group A) as compared to the diabetics with drugs (group B) and control group (C). The difference was statistically significant between groups A vs B and A vs C while the difference was statistically insignificant between groups B vs C. Keywords: Adiponectin level, Lipids, Type-2 diabetes mellitus